Tata Kelola Agile dalam Pelayanan Perpanjangan Surat Izin Mengemudi di SATPAS Colombo Kota Surabaya - Felisa Yasin, Devina Syafa; Hertati, Diana (JIAP (Jurnal Ilmu Administrasi Publik), 2026)
A driver's license (SIM) is an important document that must be possessed by motor vehicle users. A driver's license (SIM) is valid for 5 years and must be renewed after that. Therefore, public driver's license services will continue to be needed by the community. Public driver's license services are synonymous with complicated services and lengthy procedures. Surabaya, as the city with the highest number of motor vehicles in East Java, needs to provide excellent public services for driver's licenses to its citizens. The Korlantas digital application is an innovation in driver's license services. Currently, the Korlantas digital application can only be used as a service application for driver's license renewals. SATPAS Colombo, as a driver's license service location in Surabaya, is one of the locations designated to implement services based on the Korlantas digital application. This study aims to determine the agile management in the driver's license renewal service at SATPAS Colombo in Surabaya. The method used in this study is descriptive qualitative. Data collection techniques were obtained through interviews, observations, and documentation. The results of the study show that the driver's license (SIM) renewal service at SATPAS Colombo in Surabaya City can be considered agile. However, there are still obstacles such as service time that requires additional time and human resource policies that are still lacking.